Instagram @sibur.han Sebagai Media Penyebaran Edukasi Dan Informasi Burung Hantu : Analisis Konten Berdasarkan 4 Pilar Strategi Konten Media Sosial - Haryono, Diandra Rahasti; Aprianti, Agus (eProceedings of Management, 2024)
The diversity of ecosystems in Indonesia is very diverse. However, Indonesia is also experiencing a decline inbiodiversity (plants and animals), including owls. Hunting and trade of owls is one of the factors in the decline ofowl populations. In addition, understanding about owls is also still minimal. Of course, with the development oftechnology today, the dissemination of information can be done through social media. One of the social media thathas content containing information and education about owls is the @sibur.han account. The purpose of this studyis to analyze the social media content of Instagram @sibur.han as a medium for disseminating education andinformation about owls based on the 4 Pillars of Social Media Content Strategy theory, namely communication,collaboration, education, and entertainment. The method used in this research is qualitative content analysis. Basedon these 4 pillars, the @sibur.han account has covered the pillars of communication, education, and entertainment.However, uploads on the collaboration pillar are still minimal. Suggestions for further research, it is recommendedto use the interview method to further strengthen the data to be taken. Keywords-content analysis, Owl Education, 4 Pillars of Social Media Content Strategy, Instagram content.